Emerging Roles of NPQ/Spexin in Physiology and Pathology - Lv, Shuang-Yu; Zhou, Yu-Chen; Zhang, Xiao-Mei; Chen, Wei-Dong; Wang, Yan-Dong (Frontiers in Pharmacology, 2019)
Spexin (SPX), also called neuropeptide Q (NPQ), is a novel endogenous neuropeptide. Spexin gene and protein is widely expressed in central nervous system and peripheral tissues in human, rodents, goldfish, ect. A few of physiological and pathological roles of spexin are gradually emerged recently. This article summarized the roles of spexin on feeding behavior, gastrointestinal motility, obesity, diabetes, energy metabolism, endocrine, mental diseases and cardiovascular function. Given the broad roles of spexin, this neuropeptide has attracted much interest from investigators and will be as a promising future target for novel therapeutic research and drug design.